Design of a Block-Shiped Photobioreactor Based on Microalgae Chlorella vulgaris for Capturing CO2 Emissions in Indoor Environments - Adi Mulyana Supriatna; Dini Fujiyanti; Eko Prabowo Hadisantoso; Satiyarti, Rina Budi; Ashab Abdul Hakim (ORGANISMS: JOURNAL OF BIOSCIENCES, 2025)
Carbon dioxide (CO2) is one of the air polluting gases that can cause various health problems if accumulated indoors. Therefore, finding solutions to capture CO2 indoors is important. One of the efforts to reduce CO2 is by placing microalgae as CO2 capture agents in photobioreactors. This study aims to produce a photobioreactor based on microalgae Chlorella vulgaris, analyse cell density, and measure CO2 absorption by microalgae in the photobioreactor. In this study, cultivation was carried out with continuous lighting, microalgae cell density was calculated using a haemocytometer observed under a microscope, and determination of dissolved CO2 levels using the acid-base titration method in Walne medium. The results showed that a block-shaped photobioreactor with a size of 10×10×27.5 cm and a thickness of 2 mm can be a solution to capture indoor CO2 gas. The density of microalgae cells in the photobioreactor was the highest at 4.9 107 (cells/mL), indicating active photosynthesis. The results also show that the photobioreactor has the ability to capture CO2 gas in the room which is characterised by an increase in dissolved ΔCO2 levels reaching 139.39 mg/L.